(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the investigation of the personality of the aggressor criminal in the context of war criminology. A criminological typology was carried out. According to the nature and extent of political and informal power, five main types are distinguished: the supreme leader, the elite criminal, the system functionary of the highest level, the executor of the tactical level, and the ally of the highest level. A description of individual features of the individual criminological profile of an extraordinary criminal-aggressor in the person of the President of the Russian Federation V.V. Putin is given. His personality is characterized as psychopathic, psychotraumatic-necrophilic, narcissistic, prone to overcompensation; megalothyme-resentimental with reduced empathy, insensitivity to the suffering of other people; his motivations combine the desire for dominance and numinousness. It is proven that the scale of evil and the nature of the psychopathy of the current President of Russia, V.V. Putin, make him a unique social phenomenon, a socio-political, moral and psychological problem for Russia, neighboring countries, and the whole world.